LONG DISTANCE MARRIAGE (LDM) DALAM PERSPEKTIF HUKUM ISLAM - Subhan, Moh. (LP2M IAI Miftahul Ulum Pamekasan, 2022)
Marriage is a bond between two humans who have a noble goal, namely creating a family that brings peace (sakinah) and love (mawaddah wa rahmah) for all family members. In traditional community life, newly formed families live in the same house with their children or live with extended families in the same neighborhood. Along with the times, many married couples are forced to do long-distance marriages due to certain factors, one of which is work problems. A husband and wife in a long-distance marital relationship, are faced with problems regarding responsibility for the integrity of the family. With the condition of husband and wife who are far apart, it can certainly create a void of roles that should be carried out by husband and wife who live under the same roof, so that family functions experience changes. As a result of the inability to carry out these demands, it is not uncommon to cause conflicts and disputes between husband and wife who live a household like this. In undergoing a long distance marriage relationship, there are many things that are certainly burdensome considerations, one of which is the need to communicate which may be neglected and psychological and biological needs that must be met. Unfulfilled needs in marriage will result in individuals seeking fulfillment of these needs outside of marriage through infidelity and even ending in divorce. Long distance marriage in the perspective of Islamic law for married couples is jaiz/permissible, but with some conditions Keywords: Long Distance Marriage, Islamic Law